2004
DOI: 10.1007/s00417-003-0849-8
|View full text |Cite
|
Sign up to set email alerts
|

Vitrectomy with removal of the internal limiting membrane in chronic diabetic macular oedema

Abstract: Pars-plana vitrectomy with ILM peeling reduced macular oedema in most cases. In contrast, visual acuity improved significantly in 43% of the treated eyes only. The discrepancy between anatomical and functional results of ILM removal in chronic diabetic macular oedema is likely to be caused by structural changes of the macula due to long-standing oedema.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
49
1
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(55 citation statements)
references
References 25 publications
4
49
1
1
Order By: Relevance
“…Prospective studies reported 43% 6 and 52% 5 of eyes with DMO gained two or more lines of visual acuity following ILM peeling. Performing vitrectomy without ILM peeling in eyes with no evident vitreomacular traction, LaHeij et al 3 reported resolution of DMO in 21 of 21 eyes while Tachi and Ogino 4 reported resolution of DMO in 57 of 58 eyes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Prospective studies reported 43% 6 and 52% 5 of eyes with DMO gained two or more lines of visual acuity following ILM peeling. Performing vitrectomy without ILM peeling in eyes with no evident vitreomacular traction, LaHeij et al 3 reported resolution of DMO in 21 of 21 eyes while Tachi and Ogino 4 reported resolution of DMO in 57 of 58 eyes.…”
Section: Discussionmentioning
confidence: 99%
“…2 The role of vitreoretinal traction in the pathogenesis of DMO as well as positive impact of vitrectomy and removal of internal limiting membrane (ILM) on DMO has been known. [3][4][5][6] Triamcinolone-assisted posterior vitreous separation is also beneficial for DMO. 7,8 We compared the efficacy of indocyanine green (ICG)-assisted ILM peeling and triamcinolone-assisted posterior vitreous separation in terms of best-corrected visual acuity (BCVA) in DMO.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, although a recent large prospective study showed reduced oedema, only a minority of patients experienced any visual improvement. 25 A recent randomised trial of vitrectomy for macular oedema in the absence of visible traction (but with attached gel) has shown no benefit in the treatment group compared with controls treated with further grid laser. 26 The use of intravitreal triamcinolone has become very popular over the last 2 years for a number of conditions, including diffuse diabetic macular oedema.…”
Section: How Should We Treat Macular Oedema?mentioning
confidence: 99%
“…100/178 eyes (56.2%) demonstrated an acuity improvement of two or more lines at final follow-up. 24,29,30,32,39,[47][48][49] The proportion of eyes in these studies that improved by more than two lines ranged from 50 to 78%.…”
Section: Introductionmentioning
confidence: 99%